1993
DOI: 10.1037/0022-3514.65.6.1243
|View full text |Cite
|
Sign up to set email alerts
|

Social support in pregnancy: Psychosocial correlates of birth outcomes and postpartum depression.

Abstract: This prospective study examined the effects of prenatal social support on maternal and infant health and well-being in a sample of low-income pregnant women (N = 129). Three aspects of support (amount received, quality of support received, and network resources) and four outcomes (birth weight, Apgar scores, labor progress, and postpartum depression) were studied. Results indicated that women who received more support had better labor progress and babies with higher Apgar scores. Women with higher quality supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
432
5
10

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 558 publications
(485 citation statements)
references
References 72 publications
25
432
5
10
Order By: Relevance
“…These risk factors are likely to be interactive as well as multiplicative in effect. These findings are consistent with findings of previous studies such as poverty, [9] low level of education [14], more than one girl child [11], pressure and desire for a male child, high adverse life events score [8], previous psychiatric disorder [15], poor spousal relation [16], and poor support from the family [8] have been implicated as risk factors, although few studies have denied one or more of these factors as significant factors [17]. The study conducted in Chennai also indicated that PPD was significantly more in women who had unskilled husbands and had nonarranged marriages.…”
Section: Discussionsupporting
confidence: 82%
“…These risk factors are likely to be interactive as well as multiplicative in effect. These findings are consistent with findings of previous studies such as poverty, [9] low level of education [14], more than one girl child [11], pressure and desire for a male child, high adverse life events score [8], previous psychiatric disorder [15], poor spousal relation [16], and poor support from the family [8] have been implicated as risk factors, although few studies have denied one or more of these factors as significant factors [17]. The study conducted in Chennai also indicated that PPD was significantly more in women who had unskilled husbands and had nonarranged marriages.…”
Section: Discussionsupporting
confidence: 82%
“…Lack of social support, even in populations with access to modern health care, correlated in one study with lower birth weight babies, lower scores on the 5-minute Apgar test (which rates respiratory effect, muscle tone, heart rate, reflex irritability, and skin color 5 minutes after delivery), and labor difficulties (Collins et al 1993).…”
Section: Failure To Offset Puerperal Costs: Hypothesized Etiological mentioning
confidence: 99%
“…Further studies have demonstrated that satisfaction with the social support given by a woman's partner and/or family had significant beneficial effects on the later well-being of the mother and child by reducing the risk of postpartum depression [80,81] . Collins, Dunkel-Schetter [82] found social support resources during pregnancy had a substantial, statistically significant correlation between prenatal support quality and depressed mood. Evidence suggests that a lack of social support is a risk factor for postnatal depression, while strong social ties can serve as a buffer [83] .…”
Section: Social Factors Associated With Perinatal Healthmentioning
confidence: 99%